2016
DOI: 10.1016/j.jvir.2015.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Routine Antibiotic Prophylaxis for Totally Implantable Venous Access Device Placement: Meta-Analysis of 2,154 Patients

Abstract: The odds ratio of infection was 0.85 with antibiotic use but one was contained within the confidence interval suggesting no significant difference in infection rate when antibiotics were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Moreover, in a research of Johnson et al [9] including 2,154 patients undergoing TIVPC placement, 360 patients (16.7%) received antibiotic prophylaxis, while 1,794 (83.3%) received no periprocedural antibiotics. Authors identified 27 infections (1.25%) in the period after the procedure; five occurring in the antibiotic prophylaxis group (1.39%) and 22 in the nonprophylaxis group (1.23%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a research of Johnson et al [9] including 2,154 patients undergoing TIVPC placement, 360 patients (16.7%) received antibiotic prophylaxis, while 1,794 (83.3%) received no periprocedural antibiotics. Authors identified 27 infections (1.25%) in the period after the procedure; five occurring in the antibiotic prophylaxis group (1.39%) and 22 in the nonprophylaxis group (1.23%).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of formal guidelines recommending the use of preoperative prophylactic antimicrobials for port implantation, a 2013 survey by the American College of Surgery Fellows revealed that 88.2% of respondents routinely used antimicrobial prophylaxis in this setting . A meta‐analysis of 2154 patients investigated at infections related to the port within 30 days of implantation and found that, for patients who did not receive prophylactic antibiotics, the incidence of infection was 1.6% versus 1.1% in those who did receive prophylaxis . With such a low rate of events at baseline and the potential implications associated with receipt of antimicrobials, promotion of resistance, alteration of the microbiome, allergic reactions, and other adverse events, the practice of antimicrobial prophylaxis seems unwarranted until adequately powered randomized studies can support it as a beneficial and safe practice.…”
Section: Surgical Antimicrobial Prophylaxismentioning
confidence: 99%
“…Recently, the results of systematic review showed that 5 (1.39%) out of 360 patients receiving prophylactic antibiotics experienced an infection, while 22 (1.23%) out of 1794 patients who did not receive an antibiotic experienced an infection; there were no statistical differences between the two groups. This indicates that prophylactic antibiotics had no effect on postoperative infection complications[ 32 ]. Currently, relevant guidelines do not recommend the routine prophylactic use of antibiotics before or during port implantation[ 33 ].…”
Section: Clinical Questionsmentioning
confidence: 99%
“…Currently, relevant guidelines do not recommend the routine prophylactic use of antibiotics before or during port implantation[ 33 ]. Unnecessary use of antibiotics increases the risk of anaphylaxis, leads to the growth of drug-resistant microorganisms, and increases medical expenses[ 32 ].…”
Section: Clinical Questionsmentioning
confidence: 99%